An Endoplasmic Reticulum-Bound Ca(2+)/Mn(2+) Pump, ECA1, Supports Plant Growth and Confers Tolerance to Mn(2+) Stress - Wu, Zhongyi (American Society of Plant Physiologists, 2002)
Plants can grow in soils containing highly variable amounts of mineral nutrients, like Ca(2+) and Mn(2+), though the mechanisms of adaptation are poorly understood. Here, we report the first genetic study to determine in vivo functions of a Ca(2+) pump in plants. Homozygous mutants of Arabidopsis harboring a T-DNA disruption in ECA1 showed a 4-fold reduction in endoplasmic reticulum-type calcium pump activity. Surprisingly, the phenotype of mutant plants was indistinguishable from wild type when grown on standard nutrient medium containing 1.5 mm Ca(2+) and 50 μm Mn(2+). However, mutants grew poorly on medium with low Ca(2+) (0.2 mm) or high Mn(2+) (0.5 mm). On high Mn(2+), the mutants failed to elongate their root hairs, suggesting impairment in tip growth processes. Expression of the wild-type gene (CAMV35S::ECA1) reversed these conditional phenotypes. The activity of ECA1 was examined by expression in a yeast (Saccharomyces cerevisiae) mutant, K616, which harbors a deletion of its endogenous calcium pumps. In vitro assays demonstrated that Ca(2+), Mn(2+), and Zn(2+) stimulated formation of a phosphoenzyme intermediate, consistent with the translocation of these ions by the pump. ECA1 provided increased tolerance of yeast mutant to toxic levels of Mn(2+) (1 mm) and Zn(2+)(3 mm), consistent with removal of these ions from the cytoplasm. These results show that despite the potential redundancy of multiple Ca(2+) pumps and Ca(2+)/H(+) antiporters in Arabidopsis, pumping of Ca(2+) and Mn(2+) by ECA1 into the endoplasmic reticulum is required to support plant growth under conditions of Ca(2+) deficiency or Mn(2+) toxicity.